A new formalism for high spin states applied to the sd-shell region - Ragnarsson, Ingemar; Åberg, Sven; Sheline, Raymond K (Physica Scripta, 1981)
A new development within the high spin Nilsson-Strutinsky formalism presented and applied to certain sd-shell nuclei. The previous method of calculating potential-energy surfaces as a function of angular momentum using interpolated spin values is not satisfactory when studying the individual bands for these light nuclei. In the present research, manyparticle many-hole excitations are considered in the rotating system at each deformation in order to calculate the lowest energy at each spin. It is thus possible to calculate not only yrast states but also excited configurations. Potential-energy surfaces in the (ε, γ)-plane (with each grid point minimized with respect to ε4) are calculated at various values of spin, parity and signature. Special attention is paid to the problem of signature splitting (“decoupled bands”) and in some cases the two signatures are found to correspond to different shape changes of the nucleus with increasing spin. Detailed investigations of the nuclei20,22Ne,24Mg,27Al and28Si are presented.